Biological activity, UHPLC-MS phytochemical profiling, and computational studies of the leaf extract of Acridocarpus socotranus - Al-Madhagi, Wafa M.; Ali, Nasser A. Awadh; Al-Fatimi, Mohamed A.; Anwar, Sirajudheen; Ahemad, Nafees; Mansi, Iman A.; Mhaidat, Nizar M.; Al-Badani, Rowaida N.; Almarabi, Ibrahim; Naouar, Amani; Al-Balas, Qosay; Al-Khulaidi, Abdulwali (Springer Nature, 2025)
Soqotra Island is renowned for its exceptional biodiversity, harboring approximately 825 plant species, 307 of which (37%) are endemic. Despite its rich traditional knowledge, many of these plants remain scientifically underexplored. This study, for the first time, investigates the phytochemical composition, biological activities, and molecular interactions of Acridocarpus socotranus, an endemic species traditionally used to treat rheumatism and skin disorders. A comprehensive UHPLC-MS analysis of the methanol leaf extract identified 25 phytochemicals, classified into seven major categories: alkaloids, terpenoids, flavonoids, coumarins, glycosides, steroids, and other organic compounds. The extract exhibited a high phenolic content (95.6??4.90 mg GAE/g). Enzyme inhibition assays revealed that the extract effectively suppressed the activity of several enzymes, including mushroom monophenolase (IC??: 125 g/mL), diphenolase (IC??: 191.07 g/mL), xanthine oxidase (IC??: 127.8 g/mL), and glyoxalase I (IC??: 0.27 g/mL). Cytotoxicity testing showed that the extract was very effective at stopping the growth of colorectal cancer (SW480 and HCT116) cells (IC??: 259.7??12.1 and 146.3??10.9 g/mL, respectively), but it was less effective against breast cancer (MCF7 and MDA-MB-231) and prostate (PC3) cell lines (IC?? > 350 g/mL). . Molecular docking further confirmed these findings, revealing that phytochemicals from A. socotranus can effectively bind to glyoxalase I and to a conserved pocket of the salivary protein tablysin-15. The observed binding patterns resemble those of known antagonists that neutralize inflammatory mediators rather than blocking their receptors. These antagonist-like interactions suggest a potential anti-inflammatory mechanism, thereby providing additional therapeutic value.